2009
DOI: 10.1088/0957-4484/20/35/355705
|View full text |Cite
|
Sign up to set email alerts
|

Understanding effects of molecular adsorption at a single-wall boron nitride nanotube interface from density functional theory calculations

Abstract: In this paper, we explored computationally the feasibility of modulating the bandgap in a single-wall BN nanotube (BNNT) upon noncovalent adsorption of organic molecules, combined with the application of a transverse electric field. Effects of analytes' physisorption on the surface of BNNTs regarding structural and electronic properties were delineated. Relatively large binding energies were calculated, however, with minimal perturbation of the structural framework. Electronic structure calculations indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 63 publications
10
32
0
Order By: Relevance
“…[38][39][40] The interaction of glycine (Gly) with BNNTs has also been studied both in the gas phase and in microsolvated conditions. In the gas phase Gly is chemisorbed on low-diameter BNNTs through dative interactions between the NH 2 group of Gly and a B atom of the BNNTs, while it is physisorbed on large-diameter BNNTs through π-stacking dispersion interactions.…”
mentioning
confidence: 99%
“…[38][39][40] The interaction of glycine (Gly) with BNNTs has also been studied both in the gas phase and in microsolvated conditions. In the gas phase Gly is chemisorbed on low-diameter BNNTs through dative interactions between the NH 2 group of Gly and a B atom of the BNNTs, while it is physisorbed on large-diameter BNNTs through π-stacking dispersion interactions.…”
mentioning
confidence: 99%
“…Here we should point out that for small diameters, the hybridization of the electronic structure has been observed in BNNTs using DFT simulations, with band gap values lower in smaller (3, 0) and (4, 0) models compared with ultralarge ones due to πhybridization [37]. Also while for most DFT calculations the average bond length is reported at 1.44Å [38], values between 1.47 and 1.48Å have been observed for small diameters [37]. The different average bond lengths would provide a mechanical anisotropy along axial and circumferential directions, which the MM model (not based on quantum mechanics principles) would tend to underestimate.…”
Section: Molecular Mechanics Modellingmentioning
confidence: 87%
“…The figure shows that, for each tube with a fixed diameter the frequency of both zigzag and armchair tubes decreases rapidly with the rising aspect ratio α, i.e., increasing length of BNNTs. It is well known that for a clamped classical beam the frequency is calculated by [38]…”
Section: Transverse Bending Modesmentioning
confidence: 99%
“…The noncovalent functionalization of BNNTs with flavin mononucleotides showed strong p-p stacking between flavin molecule and BNNT sidewall, and fluorescence spectra demonstrated the nanohybrids to be highly fluorescent in the visible spectra (Gao et al 2011). Density functional theory (DFT) study on the noncovalent functionalization of BNNT with benzaldehyde and seven different heterocyclic aromatic molecules showed that weak interaction between the two interacting units can give rise to new impurity states within the band gap of pristine BNNTs suggesting the possibility of carrier doping via selective adsorption of aromatic rings (Akdim et al 2009). The DFT study on noncovalent adsorption of perylene derivatives on BNNT was carried out along with the subsequent charge transfer from the adsorbed molecule and BNNT (Gou et al 2010).…”
Section: Introductionmentioning
confidence: 99%